Introduction of MSMEs’ Marketplace in Lembang Marinding, Mengkendek Subdistrict, Tana Toraja Regency - As'ad, Ihwana; Fattah, Farnitawati; Djamereng, Asdar; Tenripada, Andi Ulfa (Indonesian Journal of Community Services Cel, 2023)
Lembang Marinding is a village in Mengkedek Subdistrict, Tana Toraja Regency with high potential of micro, small, and medium enterprises (MSMEs). The problem that emerges in MSMEs in Lembang Marinding is that product sales are still carried out conventionally. MSME actors in Lembang Marinding are not yet proficient in applying information technology (IT) in marketing. The community service team offers a solution by providing socialization and extension on the benefits of sell their products through digital marketing. The community service activities were carried out from October to November 2022. The target participants of these activities were the MSME actors in Lembang Marinding. The method used in overcoming problems in Lembang Marinding is mapped the MSME products in the area and provided technical training regarding how to partner with the marketplaces. One of the marketplaces chosen as partner in this training is Shopee by offering fairly easy access for beginner users to use the marketplace. The results show that the community service activities carried out by the team have successfully provided understanding, abilities, and skills to MSME actors in Lembang Marinding by introduce them to the marketplaces so that their products can be recognized by buyers outside of Tana Toraja and reach wider range of buyers. In addition, MSME actors in Lembang Marinding who participated in the training and socialization activities received modules as a guide to partner with the marketplace. The results of this activities show that MSME actors can apply technology in marketing their products, starting from how to join the marketplace to the benefits obtained.